Al doping induced high thermoelectric performance in Cu2ZnSnS4 nanoparticles synthesized by the hydrothermal method. Issue 24 (15th December 2021) - Ashfaq, Arslan; Ali, A.; Mahmood, K.; Rehman, Ubaid ur; Tahir, S.; Amin, N.; Ahmad, W.; Aslam, Rana Naveed; Arshad, Murtza; Rasheed, Kamran
Abstract: In this study, Al-doped Cu2-x Alx ZnSnS4 (x = 0%, 1%, 2%, 3%, and 4%) nanoparticles have forged using a simple hydrothermal method. The effect of Al doping on the structural, morphological, and thermoelectric properties have investigated and it has found that Al occupies the Cu site and acts as an acceptor dopant. As compared to un-doped Cu2 ZnSnS4, the electrical conductivity and Seebeck coefficient improved with the increase in Al doping concentration leads to a noticeable improvement in power factor. Meanwhile, increased grain size with the doping of higher radius atoms causes the improvement in the mobility of the charge carriers and hence electrical conductivity (27.31–36.1 S/cm). The Seebeck coefficient value has also improved by the energy filtering effect at the grain boundaries. As a result, the Al-doped sample (4%) has achieved maximum power factor value (1.82 × 10 −7 Wm −1 K −2 ), which is roughly 35% higher than pure CZTS. Graphical abstract: Image 1